The clinical recommendations of diagnostics, treatment and prevention of iron-deficiency during pregnancy and puerperal period - D O Osipchuk; S R Belomestnov; A V Kulikov (IP Berlin A.V., 2013)
The clinical recommendations summarize world experience of diagnostics, treatment and prevention of iron-deficiency during pregnancy and puerperal period.